Analysis of hair trace metal levels among workers at smelter limited company - Ade Kelana Risfiardy; Novrikasari Novrikasari; Yuanita Windusari (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Lead (Pb) is one of the heavy metals that has a negative effect on the health of the human body and the environment. This metal is included in the 20 dangerous and toxic heavy metals defined by the Environmental Protection Agency (EPA) in 1997. One way to detect exposure to lead (Pb) in the body is to analyze the levels of lead in hair. The impact of exposure to lead (Pb) can cause neurological disorders, kidney function, reproductive system function, and nerve function.Purpose: To analyze lead levels through the hair of smelter workers at the smelting department of smelter limited company on Belitung Island, Bangka Belitung Islands Province.Method: Quantitative with cross-sectional method approach. The population in this study were workers at the smelter limited company smelting division. The object of research was 30 hair samples taken using a purposive sampling method. Data analysis was processed statistically so that the research data could be concluded as univariate, bivariate, and multivariate.Results: The Fisher's exact test showed a p-value of 1,000 so it could be concluded that there was no relationship between age and Pb levels in workers' hair. There is no relationship between working duration and Pb levels in workers' hair with a p-value > 1,000. That there is no significant relationship between length of service and Pb levels in the respondent's hair with a p-value of 0.469. There is a significant relationship between smoking habits, use of PPE, and work environment with lead levels in hair with a p-value of 0.023.Conclusion: There is no relationship between age, length of work, and years of service with Pb levels in the respondent's hair because the p-value is > 0.05. And there is a relationship between the variables of smoking habits, use of PPE, and work environment with Pb levels in hair with a p-value <0.05.